Academic cultures of postgraduate supervision: what influences supervisors in their practices? - Sahar, Rafidah; Nurdamayanti, Sari; Saad, Mazni (e-International Publishing House Ltd. United Kingdom, 2022)
In this paper, we explore the academic cultures in postgraduate supervision to identify types of supervisory approaches utilized by supervisors and to determine the cultural contexts that influence theirpractice.Ourstudy is significant considering how much more nuanced and complex supervisors' responsibilities have become to accommodate postgraduates with varying backgrounds. We employed aqualitative-narrative inquiryto interview three senior supervisors at a Malaysian university. Theinterviews were then transcribed and analyzed using the holistic contentmodel. Our findings contribute to the literature on supervisory practices that would benefit postgraduates' learning experiences in Malaysia and similar contexts.